Music and Inclusion: Adapting Lessons for all Pupils - Bradaškja, Nika (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter outlines the benefits of music as a tool for promoting inclusion in schools, particularly for pupils with special needs. Music in the classroom fosters the development of social skills, enhances self-confidence, and improves the sense of belonging, facilitating the inclusion of all pupils, regardless of their special needs. It is essential for music lessons to be tailored to the needs of a diverse group of pupils, as music positively influences children's development and participation in lessons. Inclusive teaching methods that incorporate a variety of approaches, such as kinaesthetic, visual, and auditory methods, make music more comprehensible and accessible to all learners. Adaptations such as the use of specialized musical instruments, modified musical notation, and learning through movement further support the inclusion of children with diverse needs. Teachers are increasingly recognizing the importance of additional training for working with diverse groups, as the effective management of music activities helps create an inclusive learning environment where every pupil can express themselves and actively participate.